2016
DOI: 10.5897/ajb2015.14591
|View full text |Cite
|
Sign up to set email alerts
|

Development of putative transgenic lines of cassava variety H-226

Abstract: Cassava production in India is drastically affected by cassava mosaic disease (CMD) caused by the Indian cassava mosaic virus (ICMV) and Sri Lankan cassava mosaic virus (SLCMV). An attempt was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…Picloram has been reported to induce callus in many studies (Priadi and Sudarmonowati, 2006;Opabode et al, 2013;Mongomake et al, 2015;Susanti et al, 2017), which is in line with present investigation. It was noted that in both the varieties, primary callus developed from the cutting site as well as midrib of the explant, and it is in agreement with previous reports where primary callus originating from the cutting site or midrib eventually induce embryos (Anuradha et al, 2015;Ngugi et al, 2015). The observations also revealed that the colour of the callus was white in first week which later turned brown and ceased to grow.…”
Section: Discussion Discussion Discussionsupporting
confidence: 91%
“…Picloram has been reported to induce callus in many studies (Priadi and Sudarmonowati, 2006;Opabode et al, 2013;Mongomake et al, 2015;Susanti et al, 2017), which is in line with present investigation. It was noted that in both the varieties, primary callus developed from the cutting site as well as midrib of the explant, and it is in agreement with previous reports where primary callus originating from the cutting site or midrib eventually induce embryos (Anuradha et al, 2015;Ngugi et al, 2015). The observations also revealed that the colour of the callus was white in first week which later turned brown and ceased to grow.…”
Section: Discussion Discussion Discussionsupporting
confidence: 91%